Kinetic, isotherm, and possible mechanism of Pb(II) ion adsorption onto xanthated neem (Azadirachta indica) leaf powder - Mardhiah Ismail; Kamal Megat Hanafiah
Adsorption capacity is one of the concern parameters in synthesizing an adsorbent for wastewater treatment. In this research, a bio-sorbent prepared by treating neem leaf powder with a chelating agent; carbon di-sulphide (CS2 ) through xanthation reaction was synthesized. The effect of treating with ligand (CS2 ) will be investigate since ligand will bind to metal ion. Ligand or chelating agent can help in increasing the ability of adsorbent to bind a metal ion in an aqueous solution. The chemistry of adsorption of Pb(II) ion on xanthated neem leaf powder (XNL) was investigated by using batch adsorption study. The maximum adsorption capacity, 256.41 mg g-1 at 318 K was determined from isotherm study, obtained from Langmuir model. FTIR spectroscopy suggested that the adsorption of Pb(II) onto XNL could possibly occur through ion exchange, Van der Wall forces and ionic interaction.